Simultaneously refining eutectic grain and modifying eutectic Si in Al-10Si-0.3Mg alloys by Sr and CrB2 additions. (3rd May 2016) - Li, J.H.; Yang, Y.G.; Sömmez, S.; Taylor, J.A.; Oberdorfer, B.; Habe, D.; Heugenhauser, S.; Schumacher, P.
Abstract: The addition of CrB2 and Sr into Al-10Si-0.3 Mg (wt.%)-based alloys not only modify the eutectic Si, but also refine the eutectic grains. CrB2 particles were found to nucleate the eutectic grains, despite the AlP particles being partly removed or depleted by the interaction between Sr and AlP. Furthermore, P level was found to be one of the dominant factors that affect the nucleation of eutectic grains. CrB2 addition with a low P level results in a refined eutectic grain size, despite less AlP particles being present to nucleate the eutectic grains. Porosity was found to be mainly located at the boundaries of eutectic grains, highlighting the importance of the refinement of eutectic grains to reduce the size and optimise the distribution of porosity. This investigation demonstrates a novel approach to refine eutectic grains and modify eutectic Si simultaneously into Al-10Si-0.3 Mg (wt.%)-based alloys, and thereby suggests possible industrial applications.